The mIRNA519a-3p and NKG2D in endometriosis. - Cepi Teguh Pramayadi; Kanadi Sumapradja; Aria Kekalih; Muharam Natadisastra (Indonesian Socety of Obstetrics and Gynecology, 2022)
Background: Natural killer (NK) cells play a role in pathogenesis of endometriosis. Lower expressions of NK cells receptor group 2D (NKG2D) ligands inhibits cytotoxic activity of NK cells; a common immunity avoidance mechanism in neoplasms. Literatures have proven miRNAs regulatory effect on NKG2D expression. There has been no specific biomarker for diagnosing endometriosis. Non-invasive means of diagnosing endometriosis may reduce well-known risks of invasive method of diagnosis and yield better results. Purpose: To investigate the correlation between miRNA-519a-3p expression with NKG2D ligands (MICA, MICB, ULBP 1-6) on endometriosis and non-endometriosis patients. Methods: This was a cross-sectional study held in five centers: dr. Cipto Mangunkusumo General Hospital, Pelni Hospital, Bunda Hospital, YPK Mandiri Hospital, and Primaya Evasari Hospital from October 2020 to July 2021. miRNA and NKG2DL analysis were done in Human Reproduction, Infertility and Family Planning (HRIFP) cluster at IMERI FKUI. Results: We obtained 19 patients in each study groups. NKG2D ligands and miRNA519a-3p relative expressions were not significantly different (p > 0.05). Increased miRNA519a-3p expression negatively affected NKG2D ligands expression. A decrease in ULBP1 and an increase in ULBP2 increased the probability for endometriosis. NKG2D ligands expression may be influenced by infection, pro-inflammatory cytokine production, dan polymorphism. NKG2D ligands expression level can be different depending on the origin of the sample. Lower expression of miRNA519a-3p indirectly inhibits tumor apoptosis by lowering NKG2D ligands, caspase, or mRNA. Conclussion: We did not manage to establish a correlation between NKG2D ligands with miRNA519a-3p in endometriosis and non-endometriosis patients.